Temperature based rapid SAW humidity sensor - Kumar, Jitender; Kumar, Vinod; Singh, Vinay Kumar; Fahim, Fahim; Nimal, A. T. (Defence Science Journal, 2022)
This paper investigates the effect of temperature on the sensitivity of a thin-film Polyvinyl alcohol (PVA) based SAW humidity sensor. A PVA coated 433.92 MHz SAW resonator-based humidity sensor was fabricated and tested with different levels of humidity (0.5 to 95% RH) at different operating temperatures (10°C to 70°C). The sensor response was recorded through in-house developed data acquisition software and it was observed that PVA thin film coated SAW sensor shows the maximum sensitivity for trace level moisture detection at a lower temperature (≤10 °C). The sensor sensitivity has been recorded >400Hz/% RH for trace level detection (0.5–30% RH). It has been observed that sensor sensitivity deteriorates when temperature increased to 40 °C from 10 °C. The sensor has a fast response (~1s) and recovery time (<3s) for trace level humidity detection. The proposed sensor can be used in many applications, including fabrication of electronic devices, IC fabrication, pharmaceutical, textile industries, food processing, semiconductor device fabrication, and packaging.